A Mennonite Family in Tsarist Russia and the Soviet Union, 1789-1923. - Rempel, David G. (University of Toronto Press, 2003)
Rempel combines his first-hand account of life in Russian Mennonite settlements during the landmark period of 1900-1920, with a rich portrait of six generations of his ancestral family from the foundation of the first colony in 1789.